2004
DOI: 10.1007/s10561-004-1090-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and utility of new CE marked containers (CELLFLEX- MacoPharma) for bone bank

Abstract: In order to guarantee the required level of quality for our Bone &Tissue Banking, we evaluated a new CE marked container (CELLFLEX MacoPharma), for packing, transport, processing and storage of bones for therapeutic use. The use of CE marked containers is mandatory for organ and tissue containers (Medical Device Directive 93/42). We carried out a three-phase study: (1)Evaluation, (2) Implementation, (3)Audit The product was evaluated for the following criteria:Dash mechanical resistance, Dash air tightness, Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This leak test involved removal of the tamper evident seal and re-closing of the lids but still the containers did not leak. Villalba et al (2004) tested MacoPharma CELLFLEX kits for their ability to withstand prolonged storage at temperatures of À808C and below and found that the containers could withstand the temperatures without deformation but that they were not air-tight, particularly in liquid nitrogen. They did not evaluate at other temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This leak test involved removal of the tamper evident seal and re-closing of the lids but still the containers did not leak. Villalba et al (2004) tested MacoPharma CELLFLEX kits for their ability to withstand prolonged storage at temperatures of À808C and below and found that the containers could withstand the temperatures without deformation but that they were not air-tight, particularly in liquid nitrogen. They did not evaluate at other temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported on validations of tissue storage containers, Villalba et al (2004) noted that no standard test existed for this type of container. The methods used in this validation will be used in future NBS-TS validation tests of screw-top tissue containers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been quite a lot of discussions related to services, but previous studies also had a different focus, one of the results being financial ratios(Alexandros A. Papantoniou 2022) in the form of CAR, ROA and ROA before and after Branchless Banking which were significantly different, while FDR was not significantly different. In-depth understanding of the value chain will provide a competitive advantage to improve performance and profits(R. Villalba et al 2004). To produce productive competition between Islamic Banks and Conventional Banks, banking regulations(Alina Tatarenko 2006) are needed specifically for Islamic Banking so that it is able to carry out its duties without having to follow the conventional system.…”
Section: Literature Reviewmentioning
confidence: 99%